Premeiotic instability of the Neurospora crassa duplication Dp(IIIR) D305 - A Bhat; D P Kasbekar (Fungal Genetics Reports, 2002)
The duplication Dp(D305) is shown to cover the erg-3 locus (which encodes the ergosterol biosynthetic enzyme C-14 reductase). Additionally the efficiency of RIP in Dp(D305) is shown to be very low. This low efficiency may be due to the marked instability of the duplication in the premeiotic stage of the sexual cross. Premeiotic instability might also account for the low frequency with which duplication progeny are recovered from Dp(D305) x Normal crosses.